EXERGY OF TEXTILE MATERIALS - V. N. Romaniuk; D. B. Muslina (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The article presents solution for the task of evaluating exergy of the substance in the flow for textile and woven fabrics based on thermodynamic analysis of the corresponding technical systems. The exergy method allows estimating the energy effectiveness for the most problematic heat-technological systems of substance transformation and thus outlining the ways for decreasing the electric-power component in the production prime cost. The actuality of the issue stems from the renowned scenario alteration on the world energy market and is aggravated by necessity of retaining and building up the export potential of the light industry as an important component of the republic national-economic complex. The exergy method has been here for quite a long time and saw the interest fading and appearing again with periodicity of the research-generations alternation. Cooling down of every new generation towards the specified method is explained mostly by unresolved problem of the exergy evaluation for diverse materials, which poses a problem in the course of analysis of the substance transformation systems. The specified problem as a general rule does not create obstacles for energyconversion systems. However, the situation with substance-transformation systems is by far more complicated primarily due to diversity of the materials and respectively of the specification peculiarities of such component of the substance exergy in the flow as chemical component. Abeyance of conclusion in finding the chemical component of the substance exergy does not allow performing thermodynamic valuation of the energy provision for the heat-technological process in full measure. Which complicates the matters of decision-making and finding a medium for reduction of their energy consumption. All stated above relates to the textile industry and in the first instance to the finishing production departments.The authors present the exergy-evaluation problem solution for the substance in the flow for the most common fiber-types: natural animal and phytogenic ones as well as artificial fibers. Moreover, they present the solution for different colorants – basic, acid-type, dispersed. The paper considers the following components of substance exergy: reaction, concentration, and thermomechanical with presentation of their computation, correlation, and assessment deviation. The examples and exergy-computation results of the mentioned coloured fabrics are shown.